2017
DOI: 10.1007/s00726-017-2422-5
|View full text |Cite
|
Sign up to set email alerts
|

The repertoire of bitter taste receptor genes in canids

Abstract: Bitter taste receptors (Tas2rs) play important roles in mammalian defense mechanisms by helping animals detect and avoid toxins in food. Although Tas2r genes have been widely studied in several mammals, minimal research has been performed in canids. To analyze the genetic basis of Tas2r genes in canids, we first identified Tas2r genes in the wolf, maned wolf, red fox, corsac fox, Tibetan fox, fennec fox, dhole and African hunting dog. A total of 183 Tas2r genes, consisting of 118 intact genes, 6 partial genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…It is puzzling that certain hypercarnivores, such as wolves, are predicted to be more strychnine-sensitive than exclusively herbivorous animals, such as sheep and cow. However, hypercarnivores are exposed to plant material indirectly from the viscera of their prey (Shang et al, 2017 ). Ruminants, on the other hand have been found to be less sensitive to bitter taste than other mammals, which could be due to their dependence on plant-based diets which usually accompany rather high occurrence of bitterness (Ginane et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is puzzling that certain hypercarnivores, such as wolves, are predicted to be more strychnine-sensitive than exclusively herbivorous animals, such as sheep and cow. However, hypercarnivores are exposed to plant material indirectly from the viscera of their prey (Shang et al, 2017 ). Ruminants, on the other hand have been found to be less sensitive to bitter taste than other mammals, which could be due to their dependence on plant-based diets which usually accompany rather high occurrence of bitterness (Ginane et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…These functions may be related to diet change of dingoes. The candidate genes include also genes related to, e.g., reproduction and neuronal function which may have played roles in the feralization adaptation of dingoes: Prss37 (Protease, Serine 37), shown to be required for male fertility in mice 55 , ARHGEF7 (Rho Guanine Nucleotide Exchange Factor 7) which promotes the formation of neural spine and synapses in hippocampal neurons 56 , and TAS2R5 (Taste 2 Receptor Member 5) which plays a role in the perception of bitterness 57 . Interestingly, four of the genes have previously been indicated to be related to the domestication of dogs: SLC5A1 and ZNF516 were identified by Axelsson et al 20 , TAS2R5 and ZNF516 by Cagan et al 58 , and a novel gene (ENSCAFG00000023577) was found by Pendleton et al 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Functional annotation showed that four of these 13 genes are associated with neurodevelopment, metabolism and reproduction (Table 1, Supplementary Table 4). Specifically, ARHGEF7 (Rho Guanine Nucleotide Exchange Factor 7) may promote the formation of neural spine and synapses in hippocampal neurons 56 , SLC5A1 plays an important role in the absorption of glucose and sodium 59 , TAS2R5 (Taste 2 Receptor Member 5) may play a role in the perception of bitterness 57 and Prss37 (Protease, Serine 37) is related to reproduction 55 . We visualized the genotypes in 70 canine samples for these four genes.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, snakes (3,619 species) and lizards (6,263 species) comprise of 87 families, according to The Reptile Database ( http://reptile-database.org/ , last accessed July 18, 2017). Studies of taste genetics in vertebrate species have been mainly focused on mammals and birds ( Behrens, Korsching & Meyerhof, 2014 ; Behrens & Meyerhof, 2013 ; Davis et al, 2010 ; Dong, Jones & Zhang, 2009 ; Go, 2006 ; Hayakawa et al, 2012 ; Hong & Zhao, 2014 ; Jiang et al, 2012 ; Li & Zhang, 2014 ; Liu et al, 2016 ; Nei, Gu & Sitnikova, 1997 ; Feng et al, 2014 ; Shang et al, 2017 ; Shi & Zhang, 2006 ; Shi et al, 2003 ; Wang & Zhao, 2015 ; Wang, 2004 ; Wu, Chen & Rozengurt, 2005 ; Zhou, Dong & Zhao, 2009 ), however, similar studies of Tas2r genes of snakes have not been performed. The strictly carnivorous diet of snakes comprises few toxins, although it may contain defensive toxic secretions released by insects or highly toxic newts ( Brodie, Ridenhour & Iii, 2002 ; Mehrtens, 1987 ; Parker & Gans, 1978 ).…”
Section: Introductionmentioning
confidence: 99%